Audiovisual e política em Glauber e Godard: das cartografias do imaginário às oficinas de criação - Alves, Victor Gabriel Vieira (2024)
This master's dissertation, within communication studies that explore the relationship between audiovisual and politics in the research line of creative processes in communication and culture, aims to assess how studies on the imaginary in the cinema of Jean-Luc Godard and Glauber Rocha can contribute to raising awareness about the United Nations' 2030 Agenda for Sustainable Development. Specifically, the research seeks to advance the goals of SDG 4, as it proposes guidelines for the creation and application of creative workshops designed to provide accessible, inclusive, and high-quality education. Grounded in the theories of Paulo Freire, Vilém Flusser, and Lucia Leão, the project underscores the importance of integrating communicational practices, creative processes, and education as pathways to promote social justice. The dissertation assumes that cinema and audiovisual language are powerful means of fostering awareness, education, and inclusion. This study analyzes the role of Godard's and Rocha's films in promoting critical thinking and cultural access. Using Leão’s method of imaginary cartographies, in dialogue with Durand, the research focuses on key themes in Godard’s work, such as freedom, rebellion, consumerism, and social critique, and in Rocha’s work, on themes like oppression, resistance, politics, and social justice. Expected outcomes include (1) the development of cartographies; (2) critical and comparative analysis of the selected filmmakers' political propositions; and (3) the design and execution of audiovisual creative workshops informed by the research, aimed at literacy in audiovisual production within communities. The integration of Leão’s and Durand’s theories with audiovisual design processes aims not only to advance the academic field but also to contribute significantly to achieving the SDGs through inclusive and innovative educational practices